Conception and development of Self-Management indicators to advance the quality of spinal cord injury rehabilitation: SCI-High Project. (30th September 2021) - Jeyathevan, Gaya; Jaglal, Susan B.; Hitzig, Sander L.; Linassi, Gary; Mills, Sandra; Noonan, Vanessa K.; Anzai, Karen; Clarke, Teren; Wolfe, Dalton; Bayley, Mark; Aslam, Lubna; Farahani, Farnoosh; et al.
Abstract : Context: Although self-management is linked to reduced secondary health complications (SHCs) and enhanced overall quality of life post-spinal cord injury or disease (SCI/D), it is poorly integrated into the current rehabilitation process. Promoting self-management and assuring equity in care delivery is critical. Herein, we describe the selection of Self-Management structure, process and outcome indicators for adults with SCI/D in the first 18 months after rehabilitation admission. Methods: Experts in self-management across Canada completed the following tasks: (1) defined the Self-Management construct; (2) conducted a systematic search of available outcomes and their psychometric properties; and (3) created a Driver diagram summarizing available evidence related to Self-Management. Facilitated meetings allowed development and selection following rapid-cycle evaluations of proposed structure, process and outcome indicators. Results: The structure indicator is the proportion of staff with appropriate education and training in self-management principles. The process indicator is the proportion of SCI/D inpatients who have received a self-management assessment related to specific patient self-management goal(s) within 30 days of admission. The outcome indicator is the Skill and Technique Acquisition, and Self-Monitoring and Insight subscores of the modified Health Education Impact Questionnaire. Conclusion: The structure indicator will heighten awareness among administrators and policy makers regarding the need to provide staff with ongoing training related to promoting self-management skill acquisition. Successful implementation of the Self-Management process and outcome indicators will promote self-management education and skill acquisition as a rehabilitation priority, allow for personalization of skills related to the individual's self-management goal(s), and empower individuals with SCI/D to manage their health and daily activities while successfully integrating into the community.